(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
Combining baseline data of remote sensing systems active and passive has many advantages in monitoring coastal inundation dynamically. It has advanced the surface water information gaps in coastal areas, especially areas covered by clouds and shadows. The main objective of this study was to assess the dynamics of coastal inundation in Jakarta based on multi-temporal data optics of Landsat 8 and Synthetic Aperture Radar (SAR) Sentinel 1A. The method of this research used two water index algorithms. They are Modified Normalized Difference Water Index (MNDWI) and Dynamic Surface Water Extent (DSWE) based on spectral reflectance values and empirical formulas. The other method is using the coefficient backscattering of water from a single polarization of Vertical Verticals (VV) and Vertical Horizontal (VH). The study results show that the use of both satellite data baseline of 8, 9, 15, and 16 days is quite effective, applying inundation dynamics for 8-49 days. Based on the threshold value of MNDWI > 0.123 and the backscattering coefficient of -19dB are quite efficient to extract satellite data information. The empirical algorithms result in the feature of inundation, especially along the coastal dikes, reservoirs, mangrove ecosystems, and built-up lands. Satellite monitoring results show that the peak of inundation occurred on 30 May 2016 and was still visible on 15 June 2016. The combination of remote sensing methods is quite effective and efficient for monitoring inundation dynamically.